Public Participation in Establishing Legal Policy to TNCs’ Responsibility Upon the Violation of Right to Enjoy Healthy Environment in Indonesia - Sri Wartini; Jamaludin Ghofur (Fakultas Hukum Universitas Islam Indonesia, 2016)
Public participation needs to be improved to promote an access to justice when the right to enjoy a healthy environment is violated by TNCs. This article has two problem formulations: first, how is public participation in making legal policy for the responsibility of TNCs. Second, why is it necessary to design a legal policy against the responsibility of TNCs for violating the right to enjoy a healthy environment is necessary to promote an access of justice. This research is normative. The approach used was the legislation and conceptual approach. The results of this study concluded that: first, public participation in the process of issuing a legal policy for the responsibility of TNCs in Indonesia has not been implemented properly. Second, the public participation in making the legal policy against the responsibility of TNCs for violating the right to enjoy a healthy environment is necessary to promote an access of justice